MULTICOMPONENT SPECTROPHOTOMETRIC METHOD FOR SIMULTANEOUS QUANTITATION OF RANITIDINE HYDROCHLORIDE, DOMPERIDONE AND MAGALDRATE IN TABLETS - Chakraborty, Krishnasis; G., Mubeen; Kimbahune, Ritu; N., Lalitha; Karwa, Preeti (Asian Journal of Pharmaceutical Research and Development, 2016)
A fast simple precise multicomponent analytical method has been proposed for simultaneous estimation of Ranitidine hydrochloride, Domperidone and Magaldrate in tablet dosage form. Multicomponent analytical method uses inbuilt software of Spectrophotometer for measuring the absorbances at various wavelength intervals, processing and storing the data. The mixed standard and sample solutions were prepared in mixture of dilute HCl and water and scanned in the range of 200-400 nm. The absorbances were measured at four different wavelengths like 220 nm, 280 nm, 340 nm and 400 nm and concentration of each analyte was self-determined by instrument. Ranitidine hydrochloride, Domperidone and Magaldrate were found to be in the range of 99.4 - 101%, 98.8 - 100.74% and 102.2 - 103.5% respectively in the tablet dosage form. The method was validated in accordance with ICH guidelines and the results were found within the limits.